(untitled) (Jurnal Geomine, 2022)
PT Guruh Putra Bersama (GPB) is one of the mining company engaged in coal mining that applies an open pit mining system located at the Gunung Sari Village Site, Tabang District, Kutai Kartanegara Regency, East Kalimantan Province with an IUP area of 3.205 ha. In open pit mining activities, slope stability is a problem that needs to be considered for mining activities that operate every day. The condition of the slope geometry in the pit design with the actual conditions in the field is also a problem of slope stability. A safe and stable mine slope will ensure the smooth operation of mining operations, therefore it is necessary to analyze slope stability and optimal mine slope design to support a better process of mining operations. This research was conducted in the Bengkirai pit using geotechnical drill data GPBF-03 at PT Guruh Putra Bersama (GPB). Slope stability conditions at PT Guruh Putra Bersama (GPB) based on the results of slope stability analysis in the Bengkirai pit is a stable or safe slope because the FK value > 1,3. The single slope on the dumping road area has an FK value of 3,193 with a slope height of 8,6 meters and a slope angle of 51,36o. The overall slope of the Mine Situation Map and Pit Design has FK values of 3,992 and 3,286, respectively. The FK value on the overall slope has a difference of 0,706 because the two overall slope geometries are different both in height and slope angle. However, because both of the overall slopes have a value of FK> 1,3, the slope is stable and the slope geometry on the mine situation map does not need to change its dimensions.